Core Expansion of Perylenetetracarboxdiimide Dyes with Anthraquinone Units for Electron‐Accepting Materials. Issue 2 (26th November 2012) - Xu, Liang; Liu, Chao; Qin, Zhihong; Jiang, Runsheng; Li, Yongjun
Abstract: A perylenetetracarboxdiimide derivative containing an anthraquinone unit has been synthesized by the phototriggered intramolecular cyclization of 2‐anthraquinone‐substituted perylenetetracarboxdiimide. The anthraquinone‐substituted perylenetetracarboxdiimide dyes showed excellent electron‐accepting abilities with four reversible reduction potentials. Photovoltaic devices of ITO/PEDOT:PSS/P3HT:PDIs/Ca/Al were fabricated and power conversion efficiencies of 0.16 and 0.39 were obtained for1 and2, respectively. Abstract : Phototriggered intramolecular cyclization of 2‐anthraquinone‐substituted perylenetetracarboxdiimide produced a novel core‐expanded perylenetetracarboxdiimide chromophore. Their properties were investigated by optical absorption spectroscopy, electrochemistry, and theoretical calculations, and excellent electron‐accepting abilities were observed.